Stress in wild greater rhea populations: effects of agricultural activities on fecal glucocorticoid metabolite levels - Leche, A.; Bazzano, G.; Hansen, C.; Navarro, J. L.; Marin, R. H.; Martella, M. B. (2023)
Fil: Leche, A. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Diversidad y Ecología Animal; Argentina.